Terahertz orbital angular momentum modes with flexible twisted hollow core antiresonant fiber - Alessio Stefani (APL Photonics, 2018)
THz radiation is a more commonplace in research laboratories as well as in everyday life, with applications ranging from body scanners at airport security to short range wireless communications. In the optical domain, waveguides and other devices to manipulate radiation are well established. This is not yet the case in the THz regime because of the strong interaction of THz radiation with matter, leading to absorption, and the millimeter size of the wavelength and therefore of the required waveguides. We propose the use of a new material, polyurethane, for waveguides that allows high flexibility, overcoming the problem that large sizes otherwise result in rigid structures. With this material, we realize antiresonant hollow-core waveguides and we use the flexibility of the material to mechanically twist the waveguide in a tunable and reversible manner, with twist periods as short as tens of wavelengths. Twisting the waveguide, we demonstrate the generation of modes carrying orbital angular momentum. We use THz time domain spectroscopy to measure and clearly visualize the vortex nature of the mode, which is difficult in the optical domain. The proposed waveguide is a new platform offering new perspectives for THz guidance and particularly mode manipulation. The demonstrated ability to generate modes with an orbital angular momentum within a waveguide, in a controllable manner, will be beneficial to both fundamental, e.g., matter-radiation interaction, and applied, e.g., THz telecommunications, advances of THz research and technology. Moreover, this platform is not limited to the THz domain and could be scaled for other electromagnetic wavelengths.